Hubungan antara Dukungan Sosial Keluarga dengan Quarter Life Crisis pada Mahasiswa Tingkat Akhir - Ivana Abigail Weldiv Setyawan; Maria Nugraheni Mardi Rahayu (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The end of college is a transitional period toward adulthood that often causes stress and anxiety about the future. Students at this stage often feel confused about determining their direction in life and facing new demands after graduation. In this situation, family social support plays an important role in providing comfort, motivation, and confidence to face change. Based on this, this study aims to determine the relationship between family social support and quarter-life crisis in final-year students. The study employed a quantitative method with a correlational design. The participants consisted of 203 final-year students obtained through accidental sampling. The instruments used included the Developmental Crisis Questionnaire (DCQ-12) (Î± = 0.650) to measure quarter-life crisis and the Social Support Scale (SSS) (Î± = 0.959) to measure family social support. Data analysis was performed using Pearson's Product Moment correlation test after fulfilling the assumptions of normality and linearity. The results of the study show a significant negative correlation between family social support and quarter life crisis (r = -0.246; p < 0.05). This means that the higher the level of family social support received by final year students, the lower the level of quarter life crisis experienced. These findings emphasize the important role of the family in helping students face the transition to adulthood with greater preparedness and emotional balance.